Proemi, tempi e tecniche delle Storie di Livio - Bessone, Luigi (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Livy’s book I, first published on its own after January of 27, when Octavian received the title Augustus, republished probably with books II-V, to form a unified first pentad, was written roughly in the years 33-32, certainly before the battle of Actium. This is clear from certain passages and it casts light on Livy’s method, involving a long interval between writing and publication, with continuous revision of the text; books CXXI ff., editi post excessum Augusti, can thus have been composed in the years 6-14 A.D., when Livy went back to Padua.